2022
DOI: 10.3389/fpls.2022.769551
|View full text |Cite
|
Sign up to set email alerts
|

Stem Trait Spectra Underpin Multiple Functions of Temperate Tree Species

Abstract: A central paradigm in comparative ecology is that species sort out along a slow-fast resource economy spectrum of plant strategies, but this has been rarely tested for a comprehensive set of stem traits and compartments. We tested how stem traits vary across wood and bark of temperate tree species, whether a slow-fast strategy spectrum exists, and what traits make up this plant strategy spectrum. For 14 temperate tree species, 20 anatomical, chemical, and morphological traits belonging to six key stem function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 82 publications
0
20
0
2
Order By: Relevance
“…The trade‐off between hydraulic and biomechanical safety and efficiency has been frequently found in Mediterranean (Quero et al ., 2011; Ramírez‐Valiente et al ., 2020), tropical and temperate forests or tree species (Hacke et al ., 2006; van der Sande et al ., 2019; López et al ., 2021), whereas the trade‐offs across areas of temperate conifer species are rarely reported, or no such a trade‐off has been found within species (López et al ., 2013; Rosas et al ., 2019). Hence, our study supports the evidence that such a safety–efficiency spectrum is not only found across angiosperms and gymnosperms, where gymnosperms occupy the safe end of angiosperms and gymnosperms (Yang et al ., 2022), but also within gymnosperm species. We conclude that the hydraulics spectrum exists in different forest ecosystems, enabling species to adapt to divergent environments for their water use strategy in a changing climate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trade‐off between hydraulic and biomechanical safety and efficiency has been frequently found in Mediterranean (Quero et al ., 2011; Ramírez‐Valiente et al ., 2020), tropical and temperate forests or tree species (Hacke et al ., 2006; van der Sande et al ., 2019; López et al ., 2021), whereas the trade‐offs across areas of temperate conifer species are rarely reported, or no such a trade‐off has been found within species (López et al ., 2013; Rosas et al ., 2019). Hence, our study supports the evidence that such a safety–efficiency spectrum is not only found across angiosperms and gymnosperms, where gymnosperms occupy the safe end of angiosperms and gymnosperms (Yang et al ., 2022), but also within gymnosperm species. We conclude that the hydraulics spectrum exists in different forest ecosystems, enabling species to adapt to divergent environments for their water use strategy in a changing climate.…”
Section: Discussionmentioning
confidence: 99%
“…This global spectrum is well established for leaves (i.e. the leaf economics spectrum (LES)) (Wright et al ., 2004), but developed to a lesser extent for stems (Yang et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To test for the impacts of cold temperatures on bark water uptake, we conducted the same experiment in a temperate forest in Northern Spain the following winter, on the same study species ( P. sylvestris ). Finally, species vary greatly both in hydraulic wood traits and bark functional traits (Johnson et al, 2012; Rosell et al, 2014), particularly between angiosperms and gymnosperms (Yang et al, 2022), yet previous studies on bark water uptake have focused exclusively on gymnosperms (with the exception of Liu et al, 2019; performed under artificial laboratory conditions). Here, we tested for bark water uptake in an evergreen conifer ( P. sylvestris ) and in a broadleaved deciduous angiosperm ( Fagus sylvatica ), growing in the same temperate forest in Spain.…”
Section: Introductionmentioning
confidence: 99%
“…Sawdust from inner wood, outer wood and bark was collected separately, then the sawdust samples were ground in an MM400 ball mill (Retsch) and used for measurements of pH, C/N, C/P, N/P ratios, lignin concentration, nitrogen (N) and phosphorus (P) concentrations. Sampling and measurements are described in detail in Yang et al (2022).…”
Section: Sample Preparationmentioning
confidence: 99%